Bioprospecting Kluyveromyces marxianus as a Robust Host for Industrial Biotechnology - Bilal, Muhammad; Ji, Liyun; Xu, Yirong; Xu, Shuo; Lin, Yuping; Iqbal, Hafiz M. N.; Cheng, Hairong (Frontiers in Bioengineering and Biotechnology, 2022)
Kluyveromyces marxianus is an emerging non-conventional food-grade yeast that is generally isolated from diverse habitats, like kefir grain, fermented dairy products, sugar industry sewage, plants, and sisal leaves. A unique set of beneficial traits, such as fastest growth, thermotolerance, and broad substrate spectrum (i.e., hemi-cellulose hydrolysates, xylose, L-arabinose, D-mannose, galactose, maltose, sugar syrup-molasses, cellobiose, dairy industry) constitutes this yeast a particularly attractive host for applications in a variety of food and biotechnology industries. In contrast to Saccharomyces cerevisiae, most of the K. marxianus strains are apparently Crabtree-negative or having aerobic-respiring characteristics, and unlikely to endure aerobic alcoholic fermentation. This is a desirable phenotype for the large-scale biosynthesis of products associated with biomass formation because the formation of ethanol as an undesirable byproduct can be evaded under aerobic conditions. Herein, we discuss the current insight into the potential applications of K. marxianus as a robust yeast cell factory to produce various industrially pertinent enzymes, bioethanol, cell proteins, probiotic, fructose and fructo-oligosaccharides and vaccines with excellent natural features. Moreover, the biotechnological improvement and development of new biotechnological tools, particularly CRISPR–Cas9-assisted precise genome editing in K. marxianus are delineated. Lastly, the ongoing challenges, concluding remarks, and future prospects for expanding the scope of K. marxianus utilization in the modern biotechnology, food, feed, and pharmaceutical industries are also thoroughly vetted. In conclusion, it is critical to apprehend knowledge gaps around genes, metabolic pathways, key enzymes, and regulation for a complete insight into mechanism for producing relevant metabolites by K. marxianus.